Resilience in Families of Children with Physical Disabilities After Accidents - Rina Ramadhani Hasibuan; Suryanto Suryanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The family system plays an important role in facilitating or exacerbating the trauma experienced by individuals after a traumatic event. Each family has a unique approach to dealing with and resolving the various challenges that arise in their lives, especially in the context of a child's physical disability as a result of an accident. This study focuses on research to describe the strengthening of resilience in families of children with physical disabilities after an accident., and a research focus on aspects and factors that have the potential to influence it. This research uses a qualitative methodology using a descriptive approach design. Data collection techniques this study using semi-structure interviews and observation resulted in three main understandings (1) an understanding of the strengthening of families in achieving children's resilience through factors such as resilience, acceptance, adaptation, and stronger growth; (2) an understanding of the factors that influence family resilience, including internal social support from all family members, external social support from neighbors, health services, environment, communication, and trust; and (3) an understanding of the characteristics of families who achieve balance as a form of resilience.Sistem keluarga memiliki peran penting dalam memfasilitasi atau memperburuk trauma yang dialami oleh individu setelah kejadian traumatis. Setiap keluarga memiliki pendekatan yang unik dalam menangani dan menyelesaikan berbagai tantangan yang muncul dalam kehidupan mereka, terutama dalam konteks anak mengalami kecacatan fisik akibat dari kecelakaan. Penelitian ini berfokus untuk menggambarkan penguatan resiliensi pada keluarga anak penyandang disabilitas fisik setelah mengalami kecelakaan, dengan fokus penelitian pada aspek maupun faktor-faktor yang berpotensi mempengaruhinya. Penelitian menggunakan metodologi kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data menggunakan wawancara semi terstruktur dan observasi menghasilkan tiga pemahaman utama (1) pemahaman mengenai penguatan keluarga dalam mencapai ketahanan anak melalui faktor-faktor seperti ketahanan, penerimaan, adaptasi, dan pertumbuhan yang lebih kuat; (2) pemahaman mengenai faktor-faktor yang mempengaruhi ketahanan keluarga, termasuk dukungan sosial internal dari seluruh anggota keluarga, dukungan sosial eksternal dari teman sekitar, layanan kesehatan, lingkungan, komunikasi, dan kepercayaan; dan (3) pemahaman mengenai karakteristik keluarga yang mencapai keseimbangan sebagai bentuk ketahanan